2021
DOI: 10.1186/s13052-021-00959-z
|View full text |Cite
|
Sign up to set email alerts
|

Utility of a pediatric observation unit for the management of children admitted to the emergency department

Abstract: Background Observation Units (OU), as part of emergency department (ED), are areas reserved for short-term treatment or observation of patients with selected diagnoses to determine the need for hospitalization or home referral. Methods In this retrospective cohort study, we analyzed similarities and differences of children admitted to the pediatric ED of the Fondazione Policlinico Universitario A. Gemelli IRCCS hospital in the first 2 years of OU a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
2
6
0
Order By: Relevance
“…In fact, in this group, ED physicians should perform initial observation over CT scan, especially in the presence of isolated findings, no worsening of symptoms, and a child older than 3 months. Indeed, our results demonstrated that all 8 patients with ciTBI in this risk category had worsening of symptoms during clinical observation [9,16]. This is also confirmed by a secondary analysis of the PECARN head injury parent study which showed that clinical observation before CT decision-making resulted in a safe and potentially effective strategy to manage a subset of children with MHI.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In fact, in this group, ED physicians should perform initial observation over CT scan, especially in the presence of isolated findings, no worsening of symptoms, and a child older than 3 months. Indeed, our results demonstrated that all 8 patients with ciTBI in this risk category had worsening of symptoms during clinical observation [9,16]. This is also confirmed by a secondary analysis of the PECARN head injury parent study which showed that clinical observation before CT decision-making resulted in a safe and potentially effective strategy to manage a subset of children with MHI.…”
Section: Discussionsupporting
confidence: 81%
“…Our study performed in an Italian pediatric ED confirmed the efficacy and safety of the PR in detecting the presence of ciTBI in patients with MHI, reducing radiological investigations and exposure to ionizing radiations. In literature, different authors proposed clinical algorithms to optimize management of pediatric patients with MHI but the PR seems to have the best methodological quality [6][7][8][9][10][11][12][13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, stratifying patients by IBI score, 44 (26.5%) were with score (0-1) and none had a positive blood culture. Even if accepting a cautious approach for patients with low-risk IBI score and negative inflammatory markers (11 in the present series), in the remaining 33 (19.9%) invasive diagnostic procedures, broad-spectrum antibiotic therapies, and hospitalization days could be spared also with an admission to OU for 24 h [10].…”
Section: Discussionmentioning
confidence: 79%
“…Besides, 17 (5.9%) patients had been transferred to the Observation Unit (OU) [ 13 ]. The average time spent in OU was 12 h, 7/17 (41%) of these patients underwent endoscopic surgery for foreign body removal, 5/17 (29%) patients had been discharged, 5/17 (29%) patients in OU were hospitalized: two of them subsequently underwent endoscopic removal of the foreign body and three were clinically observed.…”
Section: Resultsmentioning
confidence: 99%